Antz - Darnell, Eric; John, Tim (DreamWorks Home Entertainment ; distributed in the Philippines by MagnaVision, 2004)
When Z convinces his soldier buddy Weaver to switch places with him, his simple life takes a wild turn. One of the most insignificant workers, Z may just turn out ot be the biggest hero of them all.